Carrier for electrophotography and two-component developer

By using a styrene-free acrylic resin A and a styrene-containing acrylic resin B in the electrophotographic carrier and adding fluororesin to form a stable resin coating layer, the wear resistance and charge resistance of the carrier during long-term use are solved. The problem of insufficient stability and resistance stability improves the dissipation and cohesion resistance of the carrier and extends the service life.

CN119156572APending Publication Date: 2024-12-17KANTO DENKA IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380038800.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-05-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing carriers for electrophotography have problems such as wear resistance, charging stability and resistance stability in long-term use, including insufficient wear resistance and coagulation resistance, especially when low-temperature fixing toner is used. and crosslinking, resulting in a degradation of carrier performance.

Method used

A styrene-free acrylic resin A and acrylic resin B styrene-containing component were used, and fluororesin was added to the resin coating layer, so that the styrene component in the acrylic resin was controlled to form a stable resin coating layer. , improve the dissipation resistance and coagulation resistance of the carrier.

Benefits of technology

The wear resistance, charging capacity stability and resistance stability of the carrier during long-term use are achieved, and it can effectively resist the aggregation and cross-linking of low-temperature fixing toners and extend the service life of the carrier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156572A_ABST
    Figure CN119156572A_ABST
Patent Text Reader

Abstract

The present invention relates to a carrier for electrophotography and a two-component developer using the same, the carrier for electrophotography comprising a resin-coated carrier comprising magnetic core particles and a coating layer that coats the surfaces of the core particles with a resin, the coating layer at least comprises an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin; the styrene content in the entire acrylic resin of the coating layer is less than 45.2 mass%. The ratio of the structural units derived from the styrene monomer in the acrylic resin (B) is preferably 30-90 mol% of the total structural units constituting the acrylic resin (B).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carrier for electrophotography and a two-component developer using the carrier. The carrier of the present invention is a carrier for electrostatic latent image developer. Background Art

[0002] The two-component developer for electrophotography used in the electrophotographic method is composed of a toner and a carrier, and has the following functions: the carrier is mixed and stirred with the toner in the developer tank to be frictionally charged, the toner is given a desired charge, and the charged toner is transported to the electrostatic latent image on the photoreceptor to form a toner image. In addition, the carrier is returned to the developer tank from the magnetic roller, mixed and stirred again with the newly replenished toner, and reused.

[0003] Therefore, the carrier is required to continuously exhibit the desired properties as a carrier to the toner under all environments during use, in particular, to impart stable charging properties. In view of this, a carrier having a resin coating layer formed on the surface of magnetic particles is widely used.

[0004] In the technology of copiers or printers using an electrophotographic method, the relationship between toner consumption, in which resin components or wax of the toner deteriorate during long-term printing and external additives adhere to the surface of the carrier, carrier resistance, and the charge amount of the developer is known. The increase in carrier resistance accompanying toner consumption is related to the following carrier adhesion situations: the charge on the surface of the carrier is not completely leaked just after development, and the carrier is transferred to the end when printing halftones. In addition, on the other hand, toner consumption is often related to the decrease in the charge amount of the developer.

[0005] In addition, friction between carriers, friction between carriers and developing sleeves, and contact between scrapers and carriers become more likely to occur, and the coating of the carriers is peeled off and worn, so that the core material is excessively exposed, and the resulting decrease in carrier resistance is also a problem. Similarly, the increase in carrier charge over time is also one of the problems in stable long-term printing.

[0006] As one of the techniques for stabilizing the charge amount by adjusting the composition of the coating resin, Patent Document 1 describes an electrophotographic carrier having magnetic particles and a coating layer coating the magnetic particles.

[0007] The coating layer contains: a matrix resin containing a thermoplastic acrylic resin, fluorine-containing fine particles with an average particle size of 0.1 to 0.6 μm dispersed in the matrix resin, and positively charged fine particles with an average particle size of 0.1 to 0.6 μm dispersed in the matrix resin;

[0008] The fluorine-containing fine particles contain a fluorine-containing resin having a tetrafluoroethylene unit content of 45 mol % or more based on the total amount of monomer units.

[0009] In addition, Patent Document 2 describes an electronic photographic carrier, which has a resin layer formed on the surface of magnetic particles, characterized in that the weight average molecular weight (Mw) of the resin layer is 30,000 to 150,000, and is formed by using a styrene acrylic resin, acrylic resin or methacrylic resin that is substantially soluble in a specified solvent, the inherent resistance (Ω·cm) of the electronic photographic carrier before being dissolved in the specified solvent and the inherent resistance (Ω·cm) of the electronic photographic carrier after being dissolved in the specified solvent have a specified relationship, and the shape factor (SF-1) of the electronic photographic carrier after being dissolved in the specified solvent is 110 to 130.

[0010] Furthermore, Patent Document 3 describes an electrophotographic carrier having a core material and a resin coating layer covering the surface of the core material, wherein the resin coating layer contains a resin, carbon black as conductive particles, and magnetite as conductive particles; the content of the carbon black is 0.003 to 0.525 parts by mass relative to 100 parts by mass of the core material; the content of the magnetite is 0.030 to 5.250 parts by mass relative to 100 parts by mass of the core material; and the weight ratio of the carbon black to the magnetite is 5 to 100 in terms of magnetite / carbon black. The document describes that the carrier has stable charging properties, good charge retention, and good adhesion to the core material even in multiple continuous printings.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: US-A1-2008 / 0100846

[0014] Patent Document 2: Japanese Patent Application Publication No. 2011-137867

[0015] Patent Document 3: Japanese Patent Application Publication No. 2015-138229 Summary of the invention

[0016] In recent years, in order to save energy and reduce the power of the fixing process, which consumes the most power in the electronic photography method, the use of low-temperature fixing colorants has been increasing. Compared with previous colorants, low-temperature fixing colorants are more likely to cause aggregation and agglomeration between colorants, and there is a tendency to use a large amount of external additives to suppress these situations. By using low-temperature fixing toners, there is a situation where contamination, i.e., consumption, or aggregation, i.e., the toner is welded on the surface of the carrier and cross-linked between the carriers, is more likely to occur than before. In addition, environmental considerations are further strengthened, and in order to reduce the amount of waste as a carrier, a longer life than before is desired. In this way, the characteristics required of electronic photography carriers, such as the tendency to be easily consumed or aggregated, and the need for a longer life, are increasing year by year.

[0017] From the above viewpoints, an electrophotographic carrier is desired which has good wear resistance, can achieve both charging stability and resistance stability over a long period of printing, and has high wear resistance and good aggregation resistance.

[0018] However, the inventors' research results revealed that the technology of Patent Document 1 lacks abrasion resistance, has problems such as insufficient balance between charging stability and resistance stability during long-term printing, and lacks wear resistance.

[0019] In addition, regarding Patent Document 2, a structure for achieving both resistance stability and charging stability during long-term printing and further obtaining cohesion resistance and abrasion resistance has not been studied.

[0020] Furthermore, the technology of Patent Document 3 has room for improvement in terms of fully achieving wear resistance, consumption resistance, charging stability, and resistance stability.

[0021] The object of the present invention is to solve the problems of the above-mentioned prior art and to provide a carrier having good wear resistance, good stability of carrier resistance, stable charge, good resistance to consumption and good resistance to coagulation even during long-term printing, and a developer using the carrier.

[0022] Means for solving problems

[0023] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be surprisingly solved by using, in the resin coating layer, an acrylic resin A that does not contain styrene and an acrylic resin B that contains a styrene component as acrylic resins, and further containing a fluororesin, and controlling the styrene component in the acrylic resin, thereby completing the present invention.

[0024] The present invention provides the following [1] to [6].

[0025] [1] A carrier for electrophotography, wherein in a resin-coated carrier including a core particle having magnetism and a coating layer in which the surface of the core particle is coated with a resin,

[0026] The coating layer at least comprises: an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin;

[0027] The styrene component in the entire acrylic resin in the coating layer is less than 45.2% by mass.

[0028] [2] The electrophotographic carrier according to [1], wherein the ratio of the structural unit derived from the styrene-based monomer in the acrylic resin B is 30 mol% or more and 90 mol% or less in all the structural units constituting the acrylic resin B.

[0029] [3] The electrophotographic carrier according to [1] or [2], wherein the acrylic resin A is contained in an amount of 55.0 parts by mass or more and 81.0 parts by mass or less in 100 parts by mass of the resin constituting the covering layer.

[0030] [4] The electrophotographic carrier according to any one of [1] to [3], wherein the carrier contains less than 20.0 parts by mass of the fluororesin based on 100 parts by mass of the resin constituting the covering layer.

[0031] [5] The electrophotographic carrier according to any one of [1] to [4], wherein the fluororesin is polytetrafluoroethylene.

[0032] [6] A two-component developer comprising the electrophotographic carrier according to any one of [1] to [5].

[0033] Effects of the Invention

[0034] The electrophotographic carrier of the present invention has good wear resistance, good stability of carrier resistance, stable charge, good resistance to consumption and good resistance to aggregation even during long-term printing. Therefore, the present invention can meet the demand for longer life even in the situation of easy consumption in recent years. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of a resistance measuring device used in Examples and Comparative Examples. DETAILED DESCRIPTION

[0036] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments, and can be appropriately changed and implemented within the scope of the purpose of the present invention. In addition, about the part of repeated description, there is a case where the description is appropriately omitted, but it does not limit the gist of the invention.

[0037] The present invention comprises a core material particle with magnetic properties and a coating layer of the surface of the core material particle coated with resin, and the coating layer has at least an acrylic resin A without styrene component, an acrylic resin B containing a styrene component, and a fluororesin, and the styrene component shared in all acrylic resins in the coating layer is less than 45.2% by mass. The inventors have found that, by the carrier of the present invention, even in the long-term printing resistance under the condition of easy consumption, the wear resistance is also good, the stability of the carrier resistance is also good, and the charge is also stable, the consumption resistance, and the cohesion resistance are also good. The reason is unclear, but it is believed that by making the resin solution containing the acrylic resin A without styrene component and the acrylic resin B containing styrene component coated on the magnetic particles, the acrylic resin A and the acrylic resin B form an interface with each other and are mixed, thus, the fluororesin is easily fixed to the resin coating layer, and due to this, the consumption resistance and cohesion resistance brought by the fluororesin can be brought into play, which is related to the charging stability and the resistance stability, and the resin composition is particularly suitable for improving the wear resistance.

[0038] [Core material particles]

[0039] As the core particles in the present invention, magnetic particles can be used. In the following, the core particles are also referred to as "core materials". As magnetic particles, there are no particular restrictions, and according to the purpose, they can be used from the above-mentioned ferrite group containing iron powder, magnetite, Mn ferrite, Mn-Zn ferrite, Mn-Mg ferrite, Mn-Mg-Sr ferrite, Mg ferrite, other alkali metals, alkaline earths, and light metals. If necessary, it can be appropriately used from the ferrite group that has been subjected to oxidation treatment. Among them, as the core particles, ferrite core materials are preferred, and ferrite core materials containing Mn or Mg are more preferred.

[0040] The average particle size of the core particles is not particularly limited, but is preferably 20 to 90 μm, more preferably 30 to 80 μm. The average particle size of the carrier (the carrier having a resin coating layer provided on the surface of the core particles) is also preferably 20 to 90 μm, more preferably 30 to 80 μm.

[0041] The average particle size of the core particles and the carrier can be measured using a laser diffraction particle size distribution device (HELOS (manufactured by SYMPATEC)) or a dry dispersion device (RODOS (manufactured by SYMPATEC)). In the present invention, the average particle size of the core particles and the carrier refers to the volume average particle size.

[0042] The saturation magnetization of the core particles is not particularly limited, but is preferably 20 to 110 Am 2 / kg, more preferably 30 to 100Am 2 / kg, more preferably 35 to 90Am 2 / kg. The saturation magnetization in the present invention can be measured using a vibrating sample magnetometer BHV-35H manufactured by Riken Electronics Co., Ltd. by filling a capsule (0.0565cc) with a sample and measuring it at a magnetic field of 1.1 (MA / m). In addition, the saturation magnetization of the carrier (a carrier having a resin coating layer on the surface of the core particles) is preferably 20 to 110Am 2 / kg, more preferably 30 to 100Am 2 / kg, more preferably 35 to 90Am 2 / kg.

[0043] 〔Resin coating〕

[0044] The coating layer formed by coating the surface of the core particle with a resin is also referred to as a "resin coating layer" or a "coating layer".

[0045] In the present invention, the resin constituting the resin coating layer includes an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin. Hereinafter, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid" (i.e., "acrylic acid", "methacrylic acid", or both "acrylic acid" and "methacrylic acid").

[0046] First, the acrylic resin A containing no styrene component will be described.

[0047] Examples of the acrylic resin A include acrylic polymers or derivatives thereof, and mixtures of acrylic polymers or derivatives thereof with at least one selected from acrylic monomers and acrylic oligomers. The acrylic resin A preferably does not contain fluorine.

[0048] Examples of acrylic monomers include (meth)acrylic acid, (meth)acrylic acid esters, amide-containing acrylic monomers, and (meth)acrylonitrile. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; (meth)acrylic acid esters containing hydroxyl groups such as 2-hydroxyethyl methacrylate; (meth)acrylic acid esters containing quaternary ammonium salts such as dimethylaminoethyl methacrylate methyl chloride quaternary salt or trimethylaminoethyl acrylate benzyl chloride quaternary salt. Examples of amide-containing acrylic monomers include (meth)acrylamide and N-hydroxyethyl (meth)acrylamide.

[0049] Examples of acrylic oligomers include oligomers obtained by polymerizing one or more selected from acrylic monomers. Oligomers include dimers and trimers. Oligomers generally refer to polymers having about 2 to 20 structural monomers.

[0050] Examples of acrylic polymers include polymers obtained by polymerizing the acrylic monomers and / or the acrylic oligomers. For example, examples include homopolymers formed from structural units derived from one selected from acrylic monomers; copolymers formed from structural units derived from two or more selected from acrylic monomers; and copolymers formed from structural units derived from acrylic monomers and structural units derived from monomers other than acrylic monomers and styrene monomers, wherein the copolymer is mainly composed of parts derived from acrylic monomers. Mainly composed of parts derived from acrylic monomers preferably means that the proportion of structural units derived from acrylic monomers in all structural units is 80% by mass or more, more preferably 90% by mass or more, more preferably 92% by mass or more, further preferably 95% by mass or more, and further preferably 98% by mass or more.

[0051] Examples of the derivatives of acrylic polymers include derivatives obtained by subjecting acrylic polymers to various modifications such as terminal modification or introduction of substituents, and examples of such modifications include glycidyl ether modification, introduction of ethylene oxide, hydroxyl modification, carboxyl modification, and sulfonic acid modification.

[0052] The acrylic polymer or its derivative constituting the acrylic resin A preferably has a weight average molecular weight of 5,000 to 1,000,000. The weight average molecular weight is preferably 5,000 or more so that the loss of the resin coating layer formed by the coating resin on the surface of the core particle is not excessively promoted; the weight average molecular weight is preferably 1,000,000 or less so that the charge amount is not easily reduced due to the movement of external additives from the toner particles to the surface of the carrier particles. From this point of view, the acrylic polymer or its derivative constituting the acrylic resin A more preferably has a weight average molecular weight of 7,000 or more and 500,000 or less, and particularly preferably 10,000 or more and 100,000 or less.

[0053] The weight average molecular weight can be determined as a standard polystyrene conversion value by gel permeation chromatography (GPC).

[0054] The weight average molecular weight can be obtained, for example, by using GPC (HLC-8320GPC) manufactured by Tosoh Corporation, using tetrahydrofuran as the elution solvent, polystyrene as the polystyrene standard for the calibration curve, and two TSKgel GMHXL and TSKgel Multipore HXL-M (manufactured by Tosoh Corporation) as the measurement columns.

[0055] In addition, the measurement temperature can be set to 40° C., and the flow rate can be set to 1 mL / min.

[0056] When the acrylic resin A is a mixture of an acrylic polymer or a derivative thereof and an acrylic monomer and / or an acrylic oligomer, the preferred content of the acrylic monomer and / or the acrylic oligomer is an amount such that the weight average molecular weight of the acrylic resin A after the acrylic monomer and / or the acrylic oligomer and the acrylic polymer or a derivative thereof are combined is within the above-mentioned preferred range.

[0057] From the point of view of being suitable for obtaining consumption resistance, charging stability and resistance stability, wear resistance, and cohesion resistance, as acrylic resin A, it is preferred to have a structural unit from (meth) alkyl acrylate, and the acrylic resin from the structural unit of (meth) alkyl acrylate accounts for more than 50% by mass, and it is preferred to form a moderate interface with acrylic resin B, more preferably an acrylic resin accounting for more than 70% by mass, and particularly preferably an acrylic resin accounting for more than 80% by mass, further preferably an acrylic resin accounting for more than 90% by mass, more preferably an acrylic resin accounting for more than 92% by mass, further preferably an acrylic resin accounting for more than 95% by mass, and most preferably an acrylic resin accounting for more than 98% by mass. In addition, (meth) alkyl acrylate is preferably alkyl methacrylate, in particular, more preferably methyl methacrylate or ethyl methacrylate, and most preferably methyl methacrylate. For example, PMMA is an acrylic resin A in which the structural unit from (meth) alkyl acrylate accounts for 100% by mass in all structural units.

[0058] Furthermore, “containing no styrene component” means that the structure does not contain a structural unit derived from a styrene-based monomer. A styrene-based monomer is a compound having a structure in which a vinyl group and a benzene ring are bonded, and examples thereof include the styrene-based monomers described below.

[0059] From the viewpoint of being suitable for obtaining consumption resistance, charging stability and resistance stability, wear resistance, and cohesion resistance, in the present invention, in 100 parts by mass of the resin constituting the coating layer, the acrylic resin A is preferably contained in an amount of 55 parts by mass or more and 81 parts by mass or less, more preferably 60 parts by mass or more and 81 parts by mass or less, and may also be 60 parts by mass or more and 75 parts by mass or less.

[0060] Next, the acrylic resin B containing a styrene component is described. Examples of the acrylic resin B containing a styrene component include copolymers formed by structural units derived from acrylic monomers and structural units derived from styrene monomers, or derivatives thereof. Specifically, examples include copolymers of acrylic monomers and / or acrylic oligomers, and styrene monomers and / or styrene oligomers. The acrylic resin B preferably does not contain fluorine. The copolymer with styrene monomers and / or styrene oligomers may be a random copolymer, a block copolymer, an alternating copolymer, or a graft copolymer.

[0061] Examples of the acrylic monomer include those listed in the description of the acrylic resin A.

[0062] As styrene monomers, styrene or substituted styrene can be listed; as substituted styrene, core-substituted and α-alkyl-substituted styrene can be listed. As core-substituted styrene, core-substituted styrene in which one or more hydrogen atoms bonded to the benzene ring constituting styrene are replaced by substituents such as alkyl groups having 1 to 5 carbon atoms, alkoxy groups having 1 to 5 carbon atoms, and sulfonic acid groups can be listed. Specific examples of core-substituted styrene include o-methylstyrene, p-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-n-butylstyrene, p-tert-butylstyrene, and p-chlorostyrene. In addition, as α-alkyl-substituted styrene, α-methylstyrene can be listed. As styrene oligomers, styrene oligomers obtained by polymerizing one or more selected from styrene monomers can be listed. Oligomers generally refer to polymers having about 2 to 20 structural monomers.

[0063] As the styrene-based monomer, preferably styrene and a core-substituted product or an α-substituted product in which a hydrogen atom in styrene is substituted with a substituent having 3 or less carbon atoms are mentioned, more preferably at least one selected from o-methylstyrene, p-methylstyrene and α-methylstyrene is mentioned, and styrene is most preferred.

[0064] Examples of the derivatives of the copolymers formed of the structural units derived from acrylic monomers and the structural units derived from styrene monomers include derivatives obtained by subjecting the copolymers to various modifications such as terminal modification or introduction of substituents. Examples of the modifications include glycidyl ether modification, introduction of ethylene oxide, hydroxyl modification, carboxyl modification, and sulfonic acid modification.

[0065] The weight average molecular weight of acrylic resin B is preferably 5000 to 1000000. In order not to excessively promote the loss of the resin coating layer formed by the coating resin on the surface of the core particles, the weight average molecular weight is preferably 5000 or more; in order not to cause a decrease in the charge amount caused by the movement of external additives from the colorant particles to the surface of the carrier particles, the weight average molecular weight is preferably 1000000 or less. From this point of view, the acrylic polymer or its derivative constituting acrylic resin B preferably has a weight average molecular weight of 7000 or more and 500000 or less, and particularly preferably 10000 or more and 100000 or less. The weight average molecular weight of acrylic resin B can be measured by the same method as acrylic resin A.

[0066] The ratio of the amount of acrylic resin A to acrylic resin B and the ratio of the styrene component in acrylic resin B are such that the ratio of the styrene component in the total acrylic resin becomes less than 45.2% by mass. Here, the ratio of the styrene component in the total acrylic resin specifically refers to the mass ratio of the structural unit part derived from the styrene monomer in the total amount of acrylic resin A and acrylic resin B. By making the ratio of the styrene component in the acrylic resin less than 45.2% by mass, it is possible to obtain consumption resistance, charging stability and wear resistance. From this viewpoint, the ratio of the styrene component in the total acrylic resin is preferably less than 35% by mass, and more preferably less than 30.3% by mass.

[0067] On the other hand, from the perspective of being suitable for achieving consumption resistance, charging stability and resistance stability, abrasion resistance, and cohesion resistance, the ratio of the styrene component in the total acrylic resin is preferably 4.3% by mass or more, and is also preferably 10% by mass or more, from the perspective of fully achieving the effects brought about by the above-mentioned interface.

[0068] The acrylic resin B preferably has a styrene component, i.e., a structural unit derived from a styrene-based monomer, in the total structural units of 30 mol% or more and 90 mol% or less. In order to fully obtain the effect brought about by the above-mentioned interface, it is preferably 30 mol% or more; in order to obtain abrasion resistance, it is preferably 90 mol% or less. From this point of view, the acrylic resin B more preferably has a styrene component in the total structural units of 60 mol% or more and 90 mol% or less, and particularly preferably 80 mol% or more and 90 mol% or less.

[0069] From the same viewpoint, the ratio of the structural unit derived from the acrylic monomer in all the structural units of the acrylic resin B is preferably 10 mol% to 70 mol%, more preferably 10 mol% to 40 mol%, particularly preferably 10 mol% to 20 mol%.

[0070] As the acrylic monomer used in acrylic resin B, alkyl (meth)acrylates are preferred, alkyl methacrylates are particularly preferred, methyl methacrylate or ethyl methacrylate is more preferred, and methyl methacrylate is most preferred. The acrylic monomer used in acrylic resin A and the acrylic monomer used in acrylic resin B may be the same or different.

[0071] From the perspective of being suitable for obtaining consumption resistance, charging stability and resistance stability, wear resistance, and cohesion resistance, the total amount of acrylic resin A and acrylic resin B in the resin constituting the coating layer is preferably 70 mass % or more, more preferably 80 mass % or more, and particularly preferably 82.5 mass % or more.

[0072] The styrene component in the total acrylic resin of the coating layer is less than 45.2 mass %. From the point of view of further being suitable for obtaining consumption resistance, charging stability and resistance stability, wear resistance and cohesion resistance, the amount of acrylic resin B relative to 100 mass parts of acrylic resin A is preferably greater than 1.5 mass parts and less than 50 mass parts, and further preferably greater than 3 mass parts and less than 45 mass parts.

[0073] Next, the fluororesin is described. Fluororesin is a resin containing a structural unit derived from a fluoroolefin in its structure, preferably a resin containing a structural unit derived from a perfluoroolefin in its structure, and more preferably a resin containing a structural unit derived from tetrafluoroethylene in its structure. Preferred examples of fluororesins include: homopolymers formed from structural units derived from tetrafluoroethylene, or copolymers formed from tetrafluoroethylene and structural units derived from other fluorine-containing monomers. As other fluorine-containing monomers, preferably: fluorine-containing monomers that can be copolymerized with tetrafluoroethylene. As such fluorine-containing monomers, fluoroolefins or fluoroalkyl vinyl ethers, etc., in particular, perfluoroolefins such as perfluoropropylene, or perfluoroalkyl vinyl ethers such as perfluoro(propyl vinyl ether) and perfluoro(ethyl vinyl ether), etc.

[0074] Therefore, as preferred fluororesins, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkylvinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, etc. can be mentioned.

[0075] Among them, the proportion of structural units derived from tetrafluoroethylene in the fluororesin is preferably high. The content ratio of tetrafluoroethylene units based on the total amount of monomer units in the fluororesin is preferably 50 mol% or more, more preferably 90 mol% or more, and polytetrafluoroethylene is most preferred.

[0076] The fluororesin is preferably present in the coating resin layer in the form of microparticles. When the fluororesin is microparticles, the average primary particle size thereof is preferably 0.01 to 1 μm, and more preferably 0.1 to 0.7 μm. In addition, the primary particle size of the fluororesin is the average value of the Feret diameter of the particles in the observation image obtained by a scanning electron microscope. Specifically, the magnification is preferably about 10,000 to 200,000 times, and the average value of any 50 or more particles is taken to obtain the value.

[0077] The fluororesin particles preferably have a BET specific surface area of ​​2 to 15 m 2 / g, more preferably 2 to 11 m 2 / g. The BET specific surface area of ​​the fluororesin particles was measured using nitrogen gas.

[0078] The melting point of the fluororesin is preferably 250 to 410°C. This melting point range is preferred in terms of easy uniform coverage of the core particle surface, reduced carrier surface energy, and prevention of consumption caused by toner external additives. From this viewpoint, the melting point of the fluororesin is more preferably 300 to 360°C. The so-called "melting point" herein is measured by a differential scanning calorimeter (DSC). As the weight average molecular weight of the fluororesin, it is preferably adjusted in a manner such that the melting point of the fluororesin is within the above range.

[0079] In terms of being easy to uniformly cover the surface of the core material particles with the resin constituting the coating layer, the content of the fluororesin is preferably less than 20 parts by mass, more preferably less than 17.5 parts by mass, in 100 parts by mass of the resin constituting the coating layer. In addition, from the point of view of being suitable for obtaining the effects of consumption resistance, charging stability and resistance stability, wear resistance and cohesion resistance, the content of the fluororesin is preferably more than 2.5 parts by mass, more preferably more than 5 parts by mass, in 100 parts by mass of the resin constituting the coating layer.

[0080] The covering layer may contain resins other than the above-mentioned resins, for example, silicone resins, acrylic silicone resins, etc. may be mentioned.

[0081] [Other ingredients]

[0082] In the present invention, the resin coating layer preferably contains conductive powder from the viewpoint of charging stability and resistance adjustment for obtaining a good image. From this viewpoint, the resin coating layer preferably contains carbon black.

[0083] The carbon black can be selected from ketjen black, furnace black, acetylene black, channel black, etc. Examples of commercially available products include Vulcan XC72R, REGAL330R, BLACK PEARLS2000, MONARCH 120 (all manufactured by Cabot Corporation), MA100, and MA7 (all manufactured by Mitsubishi Chemical).

[0084] The carbon black preferably has a specific surface area of ​​25 to 1500 m 2 / g. The average particle size of carbon black is preferably 100 nm or less. The average particle size of carbon black is a Feret diameter measured from a photograph taken with a transmission electron microscope, for example, an average diameter of 50 or more particles. The average particle size of carbon black is preferably 1 nm or more.

[0085] In the electrophotographic carrier of the present invention, the content of carbon black in the resin coating layer is preferably 1 to 15 parts by mass based on 100 parts by mass of the resin in the resin coating layer.

[0086] Furthermore, in the present invention, the resin coating layer may further contain an inorganic filler. According to such a configuration, the charge and resistance caused by the filler can be adjusted, and in addition, the advantages of being able to suppress changes in carrier characteristics under high temperature and high humidity environments and low temperature and low humidity environments can be obtained. Examples of the inorganic filler include hydrotalcite, silicon dioxide, titanium dioxide, magnesium oxide, aluminum oxide, zinc oxide, barium sulfate, and the like.

[0087] When the inorganic filler is hydrotalcite, the average particle size thereof is preferably 0.01 to 1.0 μm on a volume basis (cumulative volume 50% volume cumulative particle size), and more preferably 0.05 to 0.8 μm. The amount of hydrotalcite used is preferably 0.1 to 100 parts by mass, and more preferably 1 to 50 parts by mass, relative to 100 parts by mass of the resin constituting the coating layer. In addition, the volume basis D50 is measured using a laser diffraction scattering method.

[0088] When the inorganic filler is silicon dioxide, its specific surface area is preferably 10 to 400 m 2 / g, more preferably 30 to 350 m 2 The amount of silica used is preferably 0.1 to 100 parts by mass, more preferably 1 to 50 parts by mass, based on 100 parts by mass of the resin constituting the covering layer.

[0089] When the inorganic filler is titanium dioxide, its BET specific surface area is preferably 20 to 150 m 2 / g, more preferably 30 to 130 m 2 / g. The amount of titanium dioxide used is preferably 0.1 to 100 parts by mass, more preferably 1 to 50 parts by mass, based on 100 parts by mass of the resin constituting the covering layer.

[0090] When the inorganic filler is magnesium oxide, its specific surface area is preferably 0.5 to 200 m 2 / g, more preferably 0.6 to 150 m 2 / g. The amount of magnesium oxide used is preferably 0.1 to 100 parts by mass, more preferably 1 to 50 parts by mass, based on 100 parts by mass of the resin constituting the covering layer.

[0091] The amount of the inorganic filler is 0.1 to 100 parts by mass, and may be 1 to 50 parts by mass, based on 100 parts by mass of the resin constituting the covering layer.

[0092] As a method for forming a resin coating layer on the surface of the core particles, there is no particular restriction, and an impregnation method, a spraying method utilizing a fluidized bed, etc. can be appropriately used. In addition, a heat-treated process can be applied after coating, or heat-treated can be applied in a coating treatment device simultaneously with coating. When heat-treated after coating, a heat-cycle oven, a fluidized electric furnace, or a microwave heating furnace, etc. can also be used.

[0093] The amount of resin coating varies depending on the type of resin, the charging characteristics and resistance characteristics required for the carrier, but the amount of resin in the resin coating layer is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the core particles. As long as the amount of resin is 0.1 parts by mass or more, it becomes easy to evenly cover the surface of the core particles with the coating resin; as long as the amount of resin is 10 parts by mass or less, it is possible to suppress the occurrence of problems such as increased association of particles. The amount of resin is the amount of resin calculated in terms of solid content.

[0094] According to the present invention, a method for manufacturing an electrophotographic carrier is provided, which comprises a step of bringing a resin coating composition into contact with core particles, wherein the resin coating composition comprises at least three of an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin, and further comprises a liquid medium, and the styrene component in the total acrylic resin of the coating layer is less than 45.2% by mass. The manufacturing method is suitable as a method for manufacturing the electrophotographic carrier of the present invention.

[0095] In the manufacturing method, the process of contacting the resin coating composition with the core particles can be carried out by the above-mentioned method as a means for forming a resin coating layer on the surface of the core particles. In addition, the components or preferred forms contained in the resin coating composition can be appropriately selected and used from the situations described in the resin coating layer. The resin coating composition preferably contains 3 to 60% by mass of resin in terms of solid content conversion. In addition, the resin coating composition can be prepared using liquid media such as toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, butyl acetate, tetrahydrofuran, diethyl ether, acetone, N-methylpyrrolidone, etc. The resin coating composition can be used in the form of a resin solution containing such a solvent as shown in the examples. The manufacturing method may include: a process of contacting the resin coating composition with the core particles to form a resin coating layer covering the surface of the core particles.

[0096] The resistance value of the electrophotographic carrier of the present invention when 500 V is applied is preferably 1E+5 to 1E+13Ω, more preferably 1E+6 to 1E+12Ω. By setting the carrier resistance value to the above range, the following effects can be fully exerted: the carrier resistance stability is good, the charge amount is stable, the wear resistance is good, the cohesion resistance is good, and the abrasion resistance is good, so that stable printing can be achieved.

[0097] The present invention relates to a two-component developer for electrophotography containing the above-mentioned carrier for electrophotography of the present invention and a toner. As the toner, a toner manufactured by a pulverization method, a toner manufactured by a polymerization method, etc. can be used. According to the image forming device, a positively charged toner and a negatively charged toner are selected to constitute the developer, but as for the positively charged toner for the carrier for electrophotography of the present invention, a toner manufactured by using nigrosine dye or quaternary ammonium salt as a charge control agent is preferably used, and as for the negatively charged toner for the carrier for electrophotography of the present invention, a toner manufactured by using monoazo dyes, etc. is preferably used.

[0098] The toner used in the present invention can be appropriately used as a toner obtained by dispersing a colorant, a charge control agent, etc. in a binder resin. There are no particular restrictions on the binder resin, and examples thereof include polystyrene resins, styrene-acrylic resins, polyester resins, epoxy resins, polyurethane resins, etc. As colorants and charge control agents, conventionally known substances can be appropriately selected. In addition, waxes or external additives can be used as required. As external additives, inorganic particles such as silicon dioxide, titanium dioxide, aluminum oxide, titanium dioxide, zirconium oxide, and zinc oxide can be listed; or organic particles of melamine or fluorine can be listed. The so-called "two-component" developer is a convenient way to express the situation in which the developer is mainly composed of two components, a carrier and a colorant, and does not exclude the situation in which other components are contained.

[0099] Example

[0100] The present invention will be described in more detail below by way of examples and comparative examples, but the present invention is not limited thereto. In the following examples and comparative examples, the following components were used in the preparation of the coating resin solution. The units of the blending amounts in Tables 1 and 2 are parts by mass.

[0101] <Acrylic resin A>

[0102] A-1: polymethyl methacrylate (weight average molecular weight: 30,000, styrene component ratio: 0% by mass)

[0103] A-2: polymethyl methacrylate derivative (a polymethyl methacrylate derivative containing 98% by mass or more of structural units derived from methyl methacrylate, 2% by mass or less of structural units derived from (meth)acrylate containing a quaternary ammonium salt in all structural units, a weight average molecular weight of 30,000, and a styrene component ratio of 0% by mass)

[0104] A-3: polycyclohexyl methacrylate (weight average molecular weight: 50,000, styrene component ratio: 0 mass %)

[0105] <Acrylic resin B>

[0106] B-1: Methyl methacrylate / styrene copolymer, molar ratio 70 / 30 (weight average molecular weight 30,000, random copolymer)

[0107] B-2: Methyl methacrylate / styrene copolymer, molar ratio 40 / 60 (weight average molecular weight 30,000, random copolymer)

[0108] B-3: methyl methacrylate / styrene copolymer, molar ratio 10 / 90 (weight average molecular weight 30,000, random copolymer)

[0109] ·B'-1: polystyrene resin (weight average molecular weight 5500)

[0110] ·B'-2: Melamine resin (Mitsui Chemicals, Inc., U-VAN 20SE60)

[0111] <Fluororesin>

[0112] C-1: PTFE (polytetrafluoroethylene, average primary particle size: 0.3 μm, "Fluon PTFELub L170JE" manufactured by AGC Corporation, melting point: 332°C, BET specific surface area using N2: 8.2 m 2 / g. )

[0113] <Additives>

[0114] D-1: Carbon black (average particle size 30 nm, BET specific surface area 254 m 2 / g)

[0115] ·D-2: Hydrotalcite (volume basis D50: 0.1 μm)

[0116] <Other>

[0117] ·E-1: Silicon dioxide (BET specific surface area is 50m 2 / g)

[0118] E-2: Silicon dioxide (BET surface area of ​​300 m 2 / g)

[0119] ·E-3: Titanium dioxide (BET specific surface area is 50m 2 / g)

[0120] ·E-4: magnesium oxide (BET specific surface area is 130m 2 / g)

[0121] (Example 1)

[0122] 81 parts by mass of acrylic resin A-1 and 4 parts by mass of acrylic resin B-3 were added to 500 parts by mass of a solvent (toluene), mixed and dissolved at 70° C. 15 parts by mass of fluororesin C-1 was added and mixed. Furthermore, 6 parts by mass of carbon black (D-1) was added and mixed as an additive to obtain a coating resin solution.

[0123] The obtained coating resin solution was added to 100 parts by mass of a core material (MnMg ferrite, average particle size 40 μm, saturation magnetization 63 Am 2 / kg) was adjusted so that the resin solid content was 1.5 parts by mass, and sprayed using a fluidized bed coating apparatus. After the solvent was dried, heat treatment was performed at 120°C for 2 hours in a thermal circulation oven, and coarse particles were removed using a sieve with a mesh size of 75 μm to obtain a carrier of the present invention with an average particle size of 40 μm (see Table 1).

[0124] (Examples 2 to 12, Comparative Examples 1 to 7, 10, 11, 17)

[0125] The same procedure as in Example 1 was performed except that the compositions of acrylic resin A, acrylic resin B, and fluororesin C were changed as shown in Table 1 or Table 2.

[0126] (Examples 13 to 15, Comparative Examples 8, 9, and 16)

[0127] The same procedure as in Example 1 was followed except that the compositions of acrylic resin A, acrylic resin B, and fluororesin C, and the amounts and compositions of additives were changed as shown in Table 1 or Table 2.

[0128] (Examples 16 to 19)

[0129] The same procedure as in Example 4 was performed except that carbon black was added as an additive and any one of E-1 to E-4 was added in an amount described in Table 1 as other components.

[0130] (Comparative Examples 12 to 15)

[0131] The same procedure as in Example 1 was followed except that the amount and type of acrylic resin A were changed as shown in Table 2 and melamine resin or polystyrene resin in the amount described in Table 2 was used instead of acrylic resin B.

[0132] <Preparation of developer>

[0133] Under an environment of a temperature of 22° C. and a relative humidity of 55%, 7 parts by mass of a commercially available negatively charged colorant (cyan toner, for LaserJet Enterprise Color MFPM776z manufactured by HP Co., Ltd.) was placed in a V-type blender relative to 93 parts by mass of the carrier prepared in the examples or comparative examples, and stirred and mixed for 30 minutes to obtain a developer.

[0134] <Evaluation>

[0135] Next, the developer was stirred for 1 hour using a degradation device modified from a copier as a degradation treatment, and the toner was removed using a q / m-meter manufactured by Epping. The same amount of toner was then added again. Similarly, the developer was prepared and stirred using the degradation device for 4 sets, and then evaluated using the following method. When B was 2 or less and the rest was A, it was recorded as "OK"; when B was 3 or more, or C was 1 or more, it was recorded as "NO".

[0136] <Charge stability>

[0137] Compare the charge of the developer in the first and fourth degradation treatments. Use a q / m-meter manufactured by Epping to measure the friction charge Q, and calculate the AT value using the formula <AT = Q / m×T / D (Q is the friction charge, m is the mass of the developer, T is the toner concentration, and D is the weight of the developer)>. Calculate the absolute value of its change rate ((AT1-AT4) / AT1×100(%) (AT1 and AT4 are the AT values ​​after the first and fourth degradation treatments, respectively)) and evaluate using the following criteria.

[0138] A: The absolute value of the change rate is less than 10%

[0139] B: The absolute value of the change rate is greater than 10% and less than 20%

[0140] C: The absolute value of the change rate is 20% or more

[0141] <Resistance maintenance rate>

[0142] The resistance of the carrier before the degradation treatment and after the fourth degradation treatment and after the toner is removed is measured. This is done using a measuring device with N and S poles facing each other and a 6 mm interval between the magnetic poles (magnetic poles: surface magnetic flux density 1500G, facing magnetic pole area 10 mm × 30 mm). The schematic diagram of the measuring device is shown in Figure 1 In. Figure 1As shown, non-magnetic parallel plate electrodes 2, 2' (electrode area of ​​10mm×40mm, electrode spacing of 2mm) are arranged between the magnetic poles 3, 3', and 200mg of the electronic photographic carrier 1 as a sample is placed between the electrodes 2, 2', and the electronic photographic carrier 1 is held between the electrodes 2, 2' by magnetic force. The resistance value (Ω) when a DC voltage of 500V is applied is measured using an insulation resistance tester (TR-8601 manufactured by Takeda Riken), and logarithmic conversion is performed. The absolute value of the change (R0-R4 (here, R0 and R4 are the logarithmic conversion values ​​of the resistance of the carrier before degradation treatment and after degradation treatment 4 times and colorant removal)) is calculated from the logarithmic conversion value of the obtained resistance, and evaluated according to the following criteria. In addition, Figure 1 Symbol 1 in the figure is a carrier, and symbol 4 is a support platform.

[0143] A: The absolute value of the change is less than 0.5

[0144] B: The absolute value of the change is greater than 0.5 and less than 1

[0145] C: The absolute value of the change is greater than 1

[0146] <Consumption resistance>

[0147] The Si intensity of the carrier before the degradation treatment and after the degradation treatment for 4 times and the toner removal was measured using a fluorescent X-ray analyzer (ZSX Primus IV manufactured by Rigaku Corporation). The Si intensity Si0 (unit: kcps) before the degradation treatment and the Si intensity Si4 (unit: kcps) after the degradation treatment for 4 times and the toner removal were respectively obtained, and their changes (Si4-Si0) were obtained and evaluated according to the following criteria.

[0148] A: The change is less than 3kcps

[0149] B: The change is more than 3kcps and less than 4.5kcps

[0150] C: Change is 4.5kcps or more

[0151] <Agglomeration resistance>

[0152] The average particle size D50 on a volume basis was measured for each carrier before the degradation treatment and after the degradation treatment was repeated four times and the toner was removed using a dry dispersion device (RODOS (manufactured by SYMPATEC)) in a laser diffraction particle size distribution device (HELOS (manufactured by SYMPATEC)). The amount of change ((D500-D504) (μm)) was calculated from the average particle sizes D500 and D504 before the degradation treatment, after the degradation treatment was repeated four times and after the toner was removed, and the evaluation was performed according to the following criteria.

[0153] A: The change is less than 0.5μm

[0154] B: The change is 0.5 μm or more and less than 1 μm

[0155] C: Change is 1μm or more

[0156] <Abrasion resistance>

[0157] The core exposure rate was quantified by scanning electron microscopy (SEM)-image analysis. The images of 100 to 150 carrier particles were analyzed using image analysis software to determine the ratio of the area of ​​the core exposure in the carrier particle image area (exposure rate). As SEM, S-3400N manufactured by Hitachi High-Tech Corporation was used. From the exposure rates S0 and S4 before degradation treatment and after degradation treatment 4 times and toner removal, the exposure rate change (S4-S0) was determined and evaluated according to the following criteria.

[0158] A: The change is less than 3.5%

[0159] B: The change is 3.5% or more and less than 7%

[0160] C: Change is 7% or more

[0161]

[0162]

[0163] As shown in Table 1, in an electronic photographic carrier in which the coating layer comprises an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin C, and the styrene component in the total acrylic resin of the coating layer is less than 45.2% by mass, the charge is stable even after deterioration treatment, the resin peeling and resistance fluctuation are small, and the component contamination and aggregation caused by the colorant are effectively suppressed.

[0164] On the other hand, as shown in Table 2, even in Comparative Examples 1 and 2, which have acrylic resins A and B and the styrene component in the total acrylic resin is 45.2% by mass or more, the result is that the wear resistance and abrasion resistance are deteriorated. In addition, in Comparative Examples 3 to 9, which are not related to the amount of styrene component in the total acrylic resin and do not have acrylic resin A, the charging fluctuation is large, or the wear resistance, resistance maintenance rate or wear resistance is lacking. Comparative Examples 10 to 12 that do not contain acrylic resin B result in deteriorated wear resistance, and also deteriorated resistance maintenance rate and coagulation resistance, or deteriorated charging stability. Furthermore, Comparative Examples 13 to 15, which have the same styrene component ratio as the present invention in terms of the total amount of acrylic resin B and polystyrene resin mixed, also result in no wear resistance or deteriorated charging stability. Furthermore, Comparative Examples 16 and 17 that do not contain fluororesin result in deteriorated charging stability, coagulation resistance or wear resistance.

[0165] Industrial Applicability

[0166] According to the electrophotographic carrier of the present invention, charging stability, resistance stability, aggregation resistance, consumption resistance, and abrasion resistance can be fully obtained, and low-temperature fixing toner can be supported, thereby achieving a longer life of the carrier.

Claims

1. An electrophotographic carrier, wherein: In a resin-coated carrier including a core particle having magnetism and a coating layer in which the surface of the core particle is coated with a resin, The coating layer at least comprises: an acrylic resin A not containing a styrene component, an acrylic resin B containing a styrene component, and a fluororesin; The styrene component in the entire acrylic resin in the coating layer is less than 45.2% by mass.

2. The electrophotographic carrier according to claim 1, wherein The ratio of the structural unit derived from the styrene-based monomer in the acrylic resin B is 30 mol% or more and 90 mol% or less in all the structural units constituting the acrylic resin B.

3. The electrophotographic carrier according to claim 1 or 2, wherein The acrylic resin A is contained in an amount of 55.0 parts by mass or more and 81.0 parts by mass or less in 100 parts by mass of the resin constituting the covering layer.

4. The electrophotographic carrier according to claim 1 or 2, wherein The fluororesin is contained in an amount of less than 20.0 parts by mass based on 100 parts by mass of the resin constituting the covering layer.

5. The electrophotographic carrier according to claim 1 or 2, wherein The fluororesin is polytetrafluoroethylene. 6 . A two-component developer comprising the carrier for electrophotography according to claim 1 .

Citation Information

Patent Citations

  • Electrophotographic carrier and image forming method

    JP2011137867A

  • Systems and methods for all-optical signal regeneration based on free space optics

    US20080100846A1